Subsidiarity in the Australian public sector: finding pragmitism in the principle - Deem, Jacob; Brown, A.J.; Hollander, Robyn (2015)
The principle of subsidiarity, commonly understood as the view that authority should be exercised by the lowest level of government competent to do so, is a key concept in understanding and reforming Australian federalism. In this article, we explore the way in which citizens with experience working in government react to the principle, and highlight that those with experience at different levels of government approach and value subsidiarity differently. Based on mixed-methods evidence, we propose that a pragmatic, problem-oriented approach to federalism and subsidiarity may cut through these differences, and allow policymakers to come together under a unified understanding of subsidiarity. - Reproduced.
Keywords: Civil service - Australia; Federalism - Australia; Federalism